Addressing Cross-Cultural Challenges in International Student Adaptation to Higher Education - Gurung, Bishnu (My University, 2026)
There are various challenges that international students tend to experience in the process of adapting to a new academic and cultural setting. This paper discusses the adaptation of international students to higher education during one academic year, especially the cross-cultural issues. Despite the fact that students are facing academic, social, and psychological challenges, limited studies exist that explore how these challenges develop over time. This research paper answers this by delivering a deeper insight into the development of adaptation with time. The study adopts a qualitative research design. The data were gathered using semi-structured interviews with 13 international students in Finland with various academic backgrounds who had studied abroad for at least one year. Thematic analysis was applied to the data to define the main trends in the experience and adaptation process of students. The results suggest that the process of adaptation is not the same process and varies among students. Instead of taking place in distinct phases, adaptation is an evolutionary process that takes place as the students go through various interrelated issues. The respondents reported challenges in terms of language barriers, differences in academic expectations, and social integration. With the further progress of their experience, a good number of students actively formed coping strategies and routines and slowly became sure that they could cope with the academic requirements and daily life in the host environment. Nevertheless, this development did not always result in an absolute feeling of belonging since there were still certain challenges even after the first phase of integration. In addition, the issues of part-time working and the prospects of a future career were also always a matter of concern, which determined the overall experience of adapting to students. In general, the paper indicates that the adaptation of international students is a dynamic and continuous process that is affected by various factors. The results indicate that ongoing academic, social, and career assistance is essential for the universities in an effort to enhance the process of adaptation of the international students.
Keywords: adaptations; acculturation; social integration; studies in an institution of higher education; studies abroad; coping; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development